Summarising children's wellbeing: The LSAC outcome index. - Sanson, A; Misson, S (My University, 2005)
Growing Up in Australia: the Longitudinal Study of Australian Children (LSAC) is collecting a great deal of information on children's development, health and wellbeing. For the purposes of communication, it is useful to provide a summary measure of child functioning, that can then be used in comparisons of different groups (for example, sociodemographic, geographical) and to track change over time. The LSAC team has developed an Outcome Index for both the infant and 4 year old cohort on the basis of Wave 1 data. This presentation provides information about the Outcome Index and illustrates some of the ways in which it can be used.
Keywords: Health -- Wellbeing; Health; Children; Health and wellbeing; Health; Children; Wellbeing; Health and wellbeing